Answer:
The solution is ![(f^{-1})'(a) = \frac{2}{\pi }](https://tex.z-dn.net/?f=%28f%5E%7B-1%7D%29%27%28a%29%20%3D%20%5Cfrac%7B2%7D%7B%5Cpi%20%7D%20%20)
Step-by-step explanation:
From the question we are told that
The function is
, -1 < x < 1 a = 4
Here we are told find ![(f^{-1}) (a)](https://tex.z-dn.net/?f=%28f%5E%7B-1%7D%29%20%28a%29)
Let equate
![f(x) = a](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20a)
So
![4 + x^2 + tan[\frac{\pi x }{2} ] = 4](https://tex.z-dn.net/?f=4%20%2B%20%20x%5E2%20%20%2B%20tan%5B%5Cfrac%7B%5Cpi%20x%20%7D%7B2%7D%20%5D%20%3D%20%204)
![x^2 + tan[\frac{\pi x }{2} ] = 0](https://tex.z-dn.net/?f=x%5E2%20%20%2B%20tan%5B%5Cfrac%7B%5Cpi%20x%20%7D%7B2%7D%20%5D%20%20%3D%20%200)
For the equation above to be valid x must be equal to 0
Now when x = 0
![f(0) = 4+0^2 + tan [\frac{ \pi * 0}{2} ]](https://tex.z-dn.net/?f=f%280%29%20%3D%204%2B0%5E2%20%2B%20tan%20%5B%5Cfrac%7B%20%5Cpi%20%2A%200%7D%7B2%7D%20%5D)
=>
=> ![0 = f^{-1} (4)](https://tex.z-dn.net/?f=0%20%3D%20%20f%5E%7B-1%7D%20%284%29)
Differentiating f(x)
![f(x)' = 0 + 2x + sec^2 (\frac{\pi x}{2} )\cdot \frac{\pi}{2}](https://tex.z-dn.net/?f=f%28x%29%27%20%20%3D%20%200%20%2B%202x%20%20%2B%20sec%5E2%20%28%5Cfrac%7B%5Cpi%20x%7D%7B2%7D%20%29%5Ccdot%20%5Cfrac%7B%5Cpi%7D%7B2%7D)
Now
since
We have
![f(0)' = 0 + \frac{\pi }{2} sec^2 (0)](https://tex.z-dn.net/?f=f%280%29%27%20%20%3D%20%200%20%2B%20%20%5Cfrac%7B%5Cpi%20%7D%7B2%7D%20%20sec%5E2%20%280%29)
Now
![(f^{-1})'(a) = \frac{1}{(\frac{\pi}{2} )}](https://tex.z-dn.net/?f=%28f%5E%7B-1%7D%29%27%28a%29%20%3D%20%20%5Cfrac%7B1%7D%7B%28%5Cfrac%7B%5Cpi%7D%7B2%7D%20%29%7D)
![(f^{-1})'(a) = \frac{2}{\pi }](https://tex.z-dn.net/?f=%28f%5E%7B-1%7D%29%27%28a%29%20%3D%20%5Cfrac%7B2%7D%7B%5Cpi%20%7D%20%20)
D ![\bold{16x^{6}y^{10}z²}](https://tex.z-dn.net/?f=%5Cbold%7B16x%5E%7B6%7Dy%5E%7B10%7Dz%C2%B2%7D)
Answer:
John needs to rewrite the expression
. Identify which of the following is the simplified form of the expression.
![(4x^{3}y^{5}z)²](https://tex.z-dn.net/?f=%284x%5E%7B3%7Dy%5E%7B5%7Dz%29%C2%B2)
remenber that square is for all
and power is multiplied
![4²x^{3*2}y^{5*2}*z²](https://tex.z-dn.net/?f=4%C2%B2x%5E%7B3%2A2%7Dy%5E%7B5%2A2%7D%2Az%C2%B2)
![16x^{6}y^{10}z²](https://tex.z-dn.net/?f=16x%5E%7B6%7Dy%5E%7B10%7Dz%C2%B2)
Answer:
False
Step-by-step explanation:
Compound probability is the likeliness of two or more events occurring together.
Probability can never be greater than 1 whatever form it takes. Its values range between zero and one. When a probability is multiplied with any particular number such as n ( number of trials) we get expected value or whatever the formula says but probability itself is never greater than 1.
If we get the answer of any question where the found probability is greater than 1 the answer is wrong because probability is not greater than 1.
The sum of all probabilities may be nearly equal to 1 like 0.99999 etc.
THE ANSWER FOR THE MEASURE OF DEF IS A